Hemogram-derived ratios as prognostic markers of ICU admission in COVID-19 - López Escobar, Alejandro; Velázquez, Sara; Madurga, Rodrigo; Castellano, José María; Rodríguez Pascual, Jesús; Ruiz de Aguiar, Santiago; Jimeno, Sara; Montero, Juan Ignacio; Ventura Wichner, Paula Sol (My University, 2024)
Background The vast impact of COVID-19 call for the identification of clinical parameter that can help predict a torpid evolution. Among these, endothelial injury has been proposed as one of the main pathophysiological mechanisms underlying the disease, promoting a hyperinflammatory and prothrombotic state leading to worse clinical outcomes. Leukocytes and platelets play a key role in inflammation and thrombogenesis, hence the objective of the current study was to study whether neutrophil-to-lymphocyte ratio (NLR), platelets-to-lymphocyte ratio (PLR), the systemic immune-inflammation index (SII) as well as the new parameter neutrophil-to-platelet ratio (NPR), could help identify patients who at risk of admission at Intensive Care Units. Methods A retrospective observational study was performed at HM Hospitales including electronic health records from 2245 patients admitted due to COVID-19 from March 1 to June 10, 2020. Patients were divided into two groups, admitted at ICU or not. Results Patients who were admitted at the ICU had significantly higher values in all hemogram-derived ratios at the moment of hospital admission compared to those who did not need ICU admission. Specifically, we found significant differences in NLR (6.9 [4¿11.7] vs 4.1 [2.6¿7.6], p¿<¿ 0.0001), PLR (2 [1.4¿3.3] vs 1.9 [1.3¿2.9], p¿=¿0.023), NPR (3 [2.1¿4.2] vs 2.3 [1.6¿3.2], p¿<¿ 0.0001) and SII (13 [6.5¿25.7] vs 9 [4.9¿17.5], p¿<¿ 0.0001) compared to those who did not require ICU admission. After multivariable logistic regression models, NPR was the hemogram-derived ratio with the highest predictive value of ICU admission, (OR 1.11 (95% CI: 0.98¿1.22, p¿=¿0.055). Conclusions Simple, hemogram-derived ratios obtained from early hemogram at hospital admission, especially the novelty NPR, have shown to be useful predictors of risk of ICU admission in patients hospitalized due to COVID-19.